Optimizing the fluorescent protein toolbox and its use. (August 2019) - Duwé, Sam; Dedecker, Peter
Graphical abstract: Highlights: Fluorescent proteins continue to be essential tools in life sciences. Phototransformable FPs and biosensors facilitate advanced imaging experiments. Increasing experimental demands lead to a continued need for FP optimization. Abstract : Fluorescent proteins (FPs) and fluorescent protein-derived biosensors are indispensable tools in life sciences. They make it possible to probe the location, activity, or interaction of molecules of interest from a subcellular to a multicellular scale. The desire for high-resolution and multidimensional information imposes continuously increasing demands on the performance of the employed probes leading to a continued need for optimization and integration of additional features, such as phototransformable behavior. This review highlights the latest advances in FP engineering, which increase throughput and tailor the improvements directly to the envisioned experiments. Additionally, we discuss recent alternative approaches to introduce or alter phototransformable behavior and describe selected applications of phototransformable behavior in biosensors.